PENGARUH JOB DEMAND TERHADAP KINERJA ANGGOTA POLRI DENGAN VARIABEL STRES DAN BURNOUT SEBAGAI VARIABEL MEDIASI (Studi Pada Satuan Kerja Direktorat Reserse Narkoba Kepolisian Daerah Kalimantan Selatan) - Lofty Yulius Yoshua Siahaan; Hastin Umi Anisah; Rahmawati (Universitas Lambung Mangkurat, 2019)
Based on No. Perkap. 22 of 2010 about duties and functions of Ditresnarkoba is to conduct investigations and investigating drug crime. This study aims to determine and analyze the influence between job demand on the performance of Police members in Police Directorate of Drugs Investigator South Kalimantan Work Unit with burnout and stress variables as mediation variable This research method used questionnaires distributed to 57 police members who work on Ditresnarkoba South Kalimantan Police Department with 54 respondents from operational members and 3 respondents from the head of sub directorate. Measurement of this research using Likert scale with weight scale from 1 to 5 and data analysis technique using Partial Least Squares (PLS). The results showed that job demand (X1) to stress (Z1) did not affect t-statistic value <t value (1,379 <1,96), job demand (X1) on burnout (Z2) did not affect t-statistic < t value (0,712 <1,96), job demand (X1) on performance (Y) have significant effect with t-statistic value> t value (4,143> 1,96), stress (Z1) on performance (Y) has no effect the value of t-statistic <t value (0,479 <1,96), burnout (Z2) on performance (Y) has no effect on t-statistic value <t value (0,254 <1,96), stress (Z1) to burnout (Z2 ) effect with t-statistic value> t value (16,024> 1,96).